2021
DOI: 10.1021/acsomega.1c01813
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Crystal Field Modification via Incorporation of Alkali K+ Ions in YVO4:Ho3+/Yb3+ Nanophosphor and Its Hybrid with Superparamagnetic Iron Oxide Nanoparticles for Optical, Advanced Anticounterfeiting, Uranyl Detection, and Hyperthermia Applications

Abstract: In this work, we report a polyol route for easy synthesis of upconversion (UC) phosphor nanoparticles, YVO 4 :Ho 3+ -Yb 3+ -K + , which enables large-scale production and enhancement of luminescence. Upon 980 nm laser excitation, the UC emission spectrum shows a sharp bright peak at ∼650 nm of Ho 3+ ion; and the luminescence intensity increases twofold upon K + codoping. Upon 300 nm excitation, the downconversion emission spectrum shows a broad peak in the 400−500 nm range (related to the charge transfer band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The UC spectra exhibit emission bands at ∼550 nm (green = G), ∼650 nm (red = R), and ∼755 nm, and these bands arise, respectively, due to 5 F 4 , 5 S 2 → 5 I 8 , 5 F 5 → 5 I 8 , and 5 F 4 , 5 S 2 → 5 I 7 electronic transitions of the Ho 3+ ion. , Here, Yb 3+ ions are acting as sensitizers that has a higher absorption cross section as compared to Ho 3+ at 980 nm excitation. The absorption cross section of Yb 3+ is 11.7 × 10 –21 cm 2 at 980 nm excitation. , The number of photons involved in the UC is calculated and plotted as shown in Figure b. The upconverted emission intensity varies with the laser input power as I ∝ P n , where I represents the upconverted intensity, P is the laser input power, and n is the number of photons involved in the upconverted emission bands.…”
Section: Resultsmentioning
confidence: 99%
“…The UC spectra exhibit emission bands at ∼550 nm (green = G), ∼650 nm (red = R), and ∼755 nm, and these bands arise, respectively, due to 5 F 4 , 5 S 2 → 5 I 8 , 5 F 5 → 5 I 8 , and 5 F 4 , 5 S 2 → 5 I 7 electronic transitions of the Ho 3+ ion. , Here, Yb 3+ ions are acting as sensitizers that has a higher absorption cross section as compared to Ho 3+ at 980 nm excitation. The absorption cross section of Yb 3+ is 11.7 × 10 –21 cm 2 at 980 nm excitation. , The number of photons involved in the UC is calculated and plotted as shown in Figure b. The upconverted emission intensity varies with the laser input power as I ∝ P n , where I represents the upconverted intensity, P is the laser input power, and n is the number of photons involved in the upconverted emission bands.…”
Section: Resultsmentioning
confidence: 99%
“…The upconversion spectrum exhibits three strong emission peaks at ∼540, 645, and ∼750 nm, which are attributed to the electronic 4f−4f transitions 5 F 4 ( 5 S 2 ) → 5 I 8 , 5 F 5 → 5 I 8 , and 5 F 4 ( 5 S 2 ) → 5 I 7 of Ho 3+ , respectively. 17,18 It is observed that the intensity of green band emission (545 nm) is brighter than that of red band emission (645 nm) at all laser input powers. It is found that the intensity increases with the increase of laser power.…”
Section: Photoluminescence Study 241 Upconversion Emission Studymentioning
confidence: 95%
“…There is a sharp peak at 463 nm, which corresponds to the absorption peak of Ho 3+ . 17,18 It is to be noted that the band gap of NaYF 4 or NaGdF 4 is about 10 eV (∼123 nm). 23 It means that host UCNPs will be transparent above 200 nm.…”
Section: Photoluminescence Study 241 Upconversion Emission Studymentioning
confidence: 99%
“…In the case of generation of the UC emission, the most frequently used dopant ions are the following systems: Yb 3+ -Er 3+ , Yb 3+ -Tm 3+ and Yb 3+ -Ho 3+ , [45][46][47][48]; however, triple or even four-fold doped systems are also known, such as Yb 3+ -Ho 3+ -Nd 3+ and Yb 3+ -Tm 3+ -Ho 3+ -Er 3+ [49,50]. One of the most commonly studied materials is YVO 4 doped with Yb 3+ -Er 3+ .…”
Section: Introductionmentioning
confidence: 99%